The initial results of MRI-TRUS fusion prostate biopsy in high volume tertiary center - Smrkolj, Tomaž (Radiology and oncology (Ljubljana), 2024)
Background: Multiparametric magnetic resonance imaging (mpMRI) is a prerequisite for targeted prostate biopsy. The aim of our study was to evaluate the performance and learning curve of the mpMRI-transrectal ultrasound (TRUS) software image fusion (MRI-TRUS fusion) biopsy (BX) process in the first year after its introduction in our urology department. Patients and methods: MRI-TRUS fusion BX was performed in 293 patients with at least one Prostate Imaging-Reporting and Data System (PIRADS) ?3 lesion. The proportion of patients and lesions with positive histopathologic result for prostate cancer (PCa) was analyzed. The learning curve for MRI-TRUS fusion BX was assessed at institutional and individual level. Positive BX lesions were further analyzed by PIRADS and Gleason scores. Results: The proportion of patients with positive histopathologic results for targeted BX, systematic BX, and combined BX was 53.9%, 47.9%, and 63.5%, respectively. The chi-square test for the proportion of PCa positive patients showed no significant difference between the time-based patient groups at the institutional level and no significant difference between individual urologists. PIRADS score (p < 0.001), total PSA concentration (p = 0.05), prostate volume (p < 0.001) and number of cores per lesion (p = 0.034) were significant predictors of a positive histopathologic result in a lesion-based analysis. Clinically significant PCa (csPCa) was confirmed in 34.7% of the 412 BX lesions and 76.4% of the 187 positive PCa lesions. Conclusions: MRI-TRUS fusion targeted BX significantly improves the overall rate of PCa detection compared with systematic BX alone. No steep learning curve was observed in our urologists. The proportion of lesions with clinically insignificant PCa was low, limiting overdiagnosis of PCa.
Keywords: ciljana biopsija prostate; komplikacije; krivulja učenja; magnetna resonanca; rak prostate